Modern interactive technologies in the practice of teaching Ukrainian as a foreign language - Овдіюк, В. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The author analyzes the modern approaches to teaching foreign languages and the essential characteristics of the modern interactive teaching methods as effective means of forming Ukrainian communicative and social competences of foreign students. Special attention is paid to the problem of the feasibility of using various innovative technologies in the course of teaching Ukrainian as a foreign language. The attention is focused on the advantages of interactive methods of teaching over traditional methods. There have been proposed the most interesting modern methods of optimizing learning processes. Both teachers and students acknowledge an important role of using interactive methods in teaching Ukrainian as a foreign language. New techniques enable each student to take an active part in the lesson; they are means of understanding between the teacher and the student, between a student and a student; they also enable to show and intensify the knowledge. Interactive teaching methods stimulate the wish and willingness to enter the process of communication, the aspiration to understand the interlocutors in order to find compromises and the ability to realize the goals of the communicative act. Application of such methods increases the effectiveness of the educational process but most of them require a deep development and correct organization of learning activities of students. The author considers the most effective methods of modern interactive studying and substantiates feasibility of their usage. Among them: role-playing game, lesson-excursion, associative bush and use of Internet technologies.